Analysis of Heat-Insulating and Structural Building Members Behavior by the Finite Element Method - Cherednikova, Oleksandra; Avramenko, Yurii; Rozdabara, Olesia; Lapchuk, Vitaliy (International Journal of Engineering and Technology, 2018)
The paper deals with research of heat-insulating and structural elements in modern construction of Ukraine. It is established that the obtaining of theoretical models for the calculation of such type of structural elements is an economically important task that needs to be solved. The work of light polystyrene concrete slabs with profiled flooring and with different types of anchoring by finite element method (FEM) has been investigated. The method of plate models constructing for detailed study of the profiled flooring work, the material contact, their bundle, as well as the work of the reinforcement and its influence on the parameters of the stress-deformed state of polystyrene concrete and profiled flooring was proposed. Samples of light polystyrene concrete slabs with profiled flooring with different types of anchoring with the best stress-strain state characteristics were determined. The adequacy of the FEM models of plates was confirmed by comparing the results of the calculation with theoretical studies.Â Â
Keywords: Deformation property; finite element method (FEM); light concrete composite slabs; load; reinforcement; thermal insulation structure.